The use of sand as a substrate for culture of polychaeta worm Dendronereis pinnaticirris - Mustofa, Ahmad Ghufron; Harris, Enang; Supriyono, Eddy; Jusadi, Dedi (Jurnal Akuakultur Indonesia, 2012)
This experiment was conducted to study the activity, protein retention, daily growth rate, and production of Dendronereis pinnaticirris cultured in different soil substrates. Forty tested worms with average body weight of 150 mg were adapted in laboratory for 30 days. Thereafter, worms were cultured for 30 days in the 13.6 L aquaria and equipped with aeration system. A triplicate experiment was conducted using 10 cm depth of sterilized soil substrate with particle diameter of either 63‒250 μm, 250‒500 μm, or without substrate. The results showed that (1) D. pinnaticirris always swims actively when cultured in the medium without substrate, thereby resulting into the mass mortality (96.7%); (2) the substrate with particle diameter of 63‒250 μm generated significantly higher daily growth rate, survival rate, and production of D. pinnaticirris, but protein retention and feed efficiency were insignificance with those cultured in the substrate of 250–500 μm.Keywords: substrate, protein retention, production, Dendronereis pinnaticirris